Primary Closure of Gastric Perforation Using Seromuscular Omentum Insertion: A Case Report - Kalitouw, Ferry; Salem, Billy; Sugito, Brian (e-CliniC, 2024)
Abstract: Gastric perforation is the most common disease and a surgical emergency with high morbidity and mortality; therefore, early and precise management is needed. However, no consensus has been accepted regarding the best surgical treatment for gastric perforation closure so far. Although surgery methods are varied, laparotomy, and omental patch repair are still the gold standard. The risk of leakage after primary closure accompanied by omentopexy is still common, resulting high morbidity and mortality. This study aimed to discuss about the modified method by means of primary closure with seromuscular omentum insertion in a gastric perforation case. We modified the usual method using primary closure with seromuscular omentum insertion, to get the best way for perforation closure and reduced risk of leakage. After a week of surgical perforation closure, the patient was discharged and further observation resulted in no leakage. In conclusion, modified method by using primary closure with seromuscular omentum insertion in gastric perforation has good result without any leakage and recurrence. Keywords: gastric perforation; omentum; primary closure